Three-dimensional imaging and characterization of the oxide scale formed on a polycrystalline nickel-based superalloy. (1st July 2019) - Lech, Sebastian; Kruk, Adam; Gil, Aleksander; Cempura, Grzegorz; Agüero, Alina; Czyrska-Filemonowicz, Aleksandra
Abstract: Oxide scale formed on a polycrystalline nickel-based superalloy was investigated using analytical electron microscopy combined with three-dimensional tomography via conjunction of focused ion beam with scanning electron microscope. Application of these two complementary methods and correlation of the microscopy findings with three-dimensional imaging allowed to describe in detail the structure, chemistry, morphology and spatial distribution of phases and other structural elements formed during oxidation. An original approach proposed in our study allowed to identify the interlayer of the δ phase formed beneath the chromia scale and discuss formation of phases in the near-surface area and their role during oxidation. Graphical abstract: Unlabelled Image